Comparing rates of ICD-11 and DSM-5 Posttraumatic Stress Disorder in Austrian children and adolescents in foster care: prevalence, comorbidity and predictors - Paul Bruckmann; Alexander Haselgruber; Katharina Sölva; Brigitte Lueger-Schuster (European Journal of Psychotraumatology, 2020)
Background The diagnostic criteria for Posttraumatic Stress Disorder (PTSD) differ between the DSM-5 and the ICD-11, affecting prevalence and associated metrics of PTSD. Objective Investigating the effects of the diverging DSM-5 and ICD-11 PTSD conceptualizations on prevalence and comorbidity rates, as well as predictor impact in a sample of foster children and adolescents using manual-specific measures. Method The sample consisted of n = 145 foster children and adolescents. PTSD rates were assessed and compared utilizing the International Trauma Questionnaire – Child and Adolescent Version (ICD-11) and the Child and Adolescent Trauma Screen (DSM-5). PTSD comorbidities with Generalized Anxiety Disorder (GAD) and Major Depressive Disorder (MDD) were assessed. The predictive value of age, gender and cumulative trauma for PTSD was determined. Results A non-significant trend for higher DSM-5 (21.4%) vs. ICD-11 (16.7%) PTSD prevalence was observed. Significantly elevated DSM-5 vs. ICD-11 diagnostic rates were recorded in the re-experience (diff. = 18.3%) and hyperarousal (diff. = 10.1%) clusters. DSM-5 PTSD showed a non-significant trend for higher comorbidities with GAD and MDD. Gender and cumulative trauma predicted PTSD significantly and approximately equally according to both taxonomies. Conclusion The study supports the assumption that utilizing manual-specific PTSD measures in children and adolescents leads to higher rates of DSM-5 PTSD compared to ICD-11 PTSD. The exact methodological reasons for diverging diagnostic rates need to be analysed.